2014
DOI: 10.1007/s00330-014-3354-z
|View full text |Cite
|
Sign up to set email alerts
|

Suspected invasive placenta: evaluation with magnetic resonance imaging

Abstract: MR imaging has acceptable degrees of accuracy to diagnose invasive placenta. Focal uteroplacental interface defect is the best finding to diagnose invasive placenta. Focal uteroplacental interface defect is the single independent predictor of invasive placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…Eight studies explored the strength of association and the predictive accuracy of the presence of uterine bulging in recognizing the depth of placental invasion . Uterine bulging was associated with a higher risk of increta and percreta, with an OR of 6.1 and 6.3, respectively, but not of placenta accreta.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies explored the strength of association and the predictive accuracy of the presence of uterine bulging in recognizing the depth of placental invasion . Uterine bulging was associated with a higher risk of increta and percreta, with an OR of 6.1 and 6.3, respectively, but not of placenta accreta.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 984 articles were identified. After screening the abstracts, 50 full text articles were assessed with respect to their eligibility for inclusion (Supporting Information Table S2) and 16 studies were included in the systematic review (Table 1, Figure 2) (15,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). These 20 studies included 1080 pregnancies at risk for AIP, mainly because of the ultrasound suspicion of such anomalies, thus representing a population already screened for the occurrence of these disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of MRI features of the gravid uterus, Azour et al (21) indicated that the intraplacental thick T2 dark bands have been shown to be a significant feature of morbidly adherent placenta, with sensitivity and specificity of 87.9% and 71.9%, respectively; increasing volume of intraplacental dark bands on T2-weighted imaging has been shown to correspond to increasing degree of placental invasion. In a study by Bour et al (22), the intraplacental thick T2 dark bands and thinning or focal defect of the uteroplacental interface were two MRI criteria that showed both moderate interobserver agreement and significant association with invasive placenta on univariate analysis. Placenta invasion has been reported as the main factor for MRI to predict invasive placenta outcome • 177 The tenting of the bladder and/or infiltration of the pelvic organ 0.999 -UAE, uterine-artery embolization; CI, confidence interval; T2WI, T2-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports of placental abnormalities defined by MRI have appeared [33,34]. In addition, an increasing number of pregnancies are complicated by placental adhesive disorder, and clinicians are requesting imaging for the diagnosis and to aid surgical planning [35,36].…”
Section: The Placentamentioning
confidence: 99%